Strategi Pemasaran dengan Teori Permainan pada Usaha Minuman Street Boba dan Kamsia Boba - Rina Nurhidayati; Nur Arifiya; Agus Setiawan; Rifti Larasakti; Heriansyah Heriansyah (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: The purpose of this study was to determine the optimal competition between the two beverage businesses. Research Methodology: Collecting data using the questionnaire filling method and for data processing using queuing theory with pure strategy and dominant strategy. Result: Then it is found that game theory in the competition between Street Boba and Kamsia Boba is said to be optimal if the variables/attributes of service, marketing, and packaging quality on Street Boba, as well as service, marketing, and packaging quality attributes on Kamsia Boba are said to be optimal. Limitation: In this study, we will analyze the competition between the Street Boba and Kamsia Boba beverage businesses by using six attributes such as product, price, service, marketing, packaging quality, and labor. Contribution: This research can contribute to economic and academic development. In terms of economics, this research can be used to understand a good marketing strategy for business actors. And in the academic field, it can be used by academics to learn more about the methods used.